Analisa Algoritma Kriptografi Klasik Caesar Cipher Viginere Cipher dan Hill Cipher – Study Literature - Noviyanti. P; Mira (Institut Shanti Bhuana, 2022)
The process of encryption and description of a message is a third party called cryptography. Cryptography is a technique for securely transferring information between two parties without intervention by external elements. The process of securing information can be done with several available cryptographic algorithms. Cryptographic algorithms consist of two eras, namely, classical algorithms and modern algorithms. Classical algorithms were generally used in the past using only substitution and permutation methods. While modern algorithms are algorithms that can be recognized, read and understood by computers that produce the numbers 0 and 1 or commonly called binary data. The purpose of the analysis is to determine the development of security and complexity of standard classical algorithms and classical algorithms with modifications.